An operational-mode-based method for estimating ship emissions in port waters. (December 2021) - Chen, Shukai; Meng, Qiang; Jia, Peng; Kuang, Haibo
Highlights: Propose an operational-mode-based method for ship emission estimation. Customize an algorithm to recognize both berthing and un-berthing services of tugs. Use automatic identification system (AIS) data of Dalian Port for a case study. Abstract: The operational modes of ships reflect the status of ship engines and thus greatly impact the rate of emissions. To capture the characteristics of ship emissions, this study proposes an operational-mode-based method for estimating ship emission inventory. The operational modes of ships are classified according to automatic identification system (AIS) data. An effective algorithm is tailored to identify the operational modes of tugs (berthing, un-berthing, and maneuver). For cargo ships and passenger ships, three key operational modes are considered (transit, maneuver, and hotelling). Based on the identified operational modes, different methods (propeller-law-based method or empirical rules) are applied for emission estimation. In the case study, the ship emissions in the waters of the Port of Dalian are calculated. The results imply that port operators can reduce the emissions by limiting the sulfur content in fuel oil and requiring tugs to perform pushing and pulling operations with a lower engine load.